Detection of Plasmodium Aldolase Using a Smartphone and Microfluidic Enzyme Linked Immunosorbent Assay. (6th September 2017) - Gopal, Nikhil S.; Raychaudhuri, Ruben
Abstract : Background . Malaria control efforts are limited in rural areas. A low-cost system to monitor response without the use of electricity is needed. Plasmodium aldolase is a malaria biomarker measured using enzyme linked immunosorbent assay (ELISA) techniques. A three-part system using ELISA was developed consisting of a microfluidic chip, hand crank centrifuge, and a smartphone. Methods. A circular microfluidic chip was fabricated using clear acrylic and a CO2 laser. A series of passive valves released reagents at precise times based upon centrifugal force. Color change was measured via smartphone camera using an application programmed in Java. The microchip was compared to a standard 96-well sandwich ELISA. Results . Results from standard ELISA were compared to microchip at varying concentrations (1–10 ng/mL). Over 15 different microfluidic patterns were tested, and a final prototype of the chip was created. The prototype microchip was compared to standard sandwich ELISA (n = 20 ) using samples of recombinant aldolase. Color readings of standard ELISA and microfluidic microchip showed similar results. Conclusion . A low-cost microfluidic system could detect and follow therapeutic outcomes in rural areas and identify resistant strains.